Teaching and Assessing Intercultural Communicative Competence: Revisited - Byram, Michael (Channel View Publications, 2020)
This revised edition of Michael Byram's classic 1997 book updates the text in light of both recent research and critiques and commentaries on the 1st edition. Beginning from the premise that foreign and second language teaching should prepare learners to use a language with fluency and accuracy, and also to speak with people who have different cultural identities, social values and behaviours, the book is an invaluable guide for teachers and curriculum developers, taking them from a definition of Intercultural Communicative Competence through planning for teaching to assessment. This edition refines the definitions of the five 'savoirs' of intercultural competence, and includes new sections on issues such as moral relativism and human rights, mediation, intercultural citizenship and teachers' ethical responsibilities.